2019
DOI: 10.1016/j.neurobiolaging.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive aging is not created equally: differentiating unique cognitive phenotypes in “normal” adults

Abstract: Age-related cognitive decline is a public health problem, but highly diverse and difficult to predict. We captured non-overlapping cognitive phenotypes in high-functioning adults and identified baseline factors differentiating trajectories. 314 functionally normal adults (M=69y) completed 2+ visits. Participants with sample-based longitudinal slopes in memory or processing speed <−1SD were classified as "declining" on that measure. 29 and 50 individuals fell <−1SD on processing speed or memory slopes, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 53 publications
0
47
0
2
Order By: Relevance
“…Indeed, the study of Yokoyama et al was the only study that reported on genetic factors of cognitive maintenance [29]. There is a total of 11 studies that looked at biological measures in relation to cognitive trajectories including neuroimaging, genetic, blood and autoptic biomarkers [20,28,29,31,34,35,38,43,50,52,69]. However, APOE 4 allele and amyloid load are the only two biomarkers which were tested in two or more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the study of Yokoyama et al was the only study that reported on genetic factors of cognitive maintenance [29]. There is a total of 11 studies that looked at biological measures in relation to cognitive trajectories including neuroimaging, genetic, blood and autoptic biomarkers [20,28,29,31,34,35,38,43,50,52,69]. However, APOE 4 allele and amyloid load are the only two biomarkers which were tested in two or more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with premenopausal women, menopausal women express a wide range of psychological symptoms including poor memory and concentration, depression, anxiety, insomnia, fatigue, irritability, and a high level of distress, which may impede coping and decrease quality of life in this group [5]. Furthermore, severe neuropsychiatric symptoms may reflect the development of age-related pathologies such as cognitive impairment associated with Alzheimer's disease, especially during the prodromal stage, but get misinterpreted as symptoms of natural aging and go uncared for [6], which can have serious health-related drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies that address sex differences in older humans generally indicate poorer episodic memory in men. There is a debate concerning sex differences in the trajectory of cognitive impairments, with results indicating no difference or a steeper decline in males (Finkel et al, 2003;Ferreira et al, 2014;Lundervold et al, 2014;McCarrey et al, 2016;Olaya et al, 2017;Hughes et al, 2018;Lee et al, 2018;Casaletto et al, 2019). Cross-sectional rodent studies indicate age and sex differences in tasks that involve repeated acquisition of spatial information and episodic memory (Lukoyanov et al, 1999;Markowska, 1999;Rossetti et al, 2018); nevertheless, most longitudinal studies in animal models of aging have not compared sex differences in the decline of memory.…”
Section: Introductionmentioning
confidence: 99%